Frecuencia y número de fármacos necesarios en pacientes con hipertensión arterial controlada que asistan a consulta externa del Hospital Teófilo Dávila - Galarza San Martín, Lisbeth M. (2012)
Using a cross-sectional study 95 hypertensive patients presenting for care at hospital outpatient Teófilo Dávila in 2011, information is obtained by collecting data directly into an outpatient whose overall objective is to determine the percentage of hypertensive patients have blood pressure controlled outpatient and specific objectives to determine which drug combination get to have controlled hypertension such patients.